Behavioural reactivity and ensuing temperamental traits in young thoroughbred racehorses (Equus caballus) - McGee, Sieglinde (Trinity College (Dublin, Ireland). School of Psychology, 2005)
This thesis is the culmination of a four-year research project carried out through the Department of Psychology in the University of Dublin, Trinity College and in which behavioural reactivity and ensuing temperamental traits were assessed in young thorough bred racehorses (Equus caballus).
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin